Randomized, multicenter trial to assess the efficacy, safety and tolerability of a single dose of a novel AMPA receptor antagonist BGG492 for the treatment of acute migraine attacks. (February 2014) - Gomez-Mancilla, Baltazar; Brand, Ronald; Jürgens, Tim P; Göbel, Harmut; Sommer, Claudia; Straube, Andreas; Evers, Stefan; Sommer, Martin; Campos, Victor; Kalkman, Hans O; Hariry, Sam; Pezous, Nicole; et al.
Background: Glutamate is implicated in migraine pathophysiology; amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptor antagonists represent a potential therapeutic approach because of their anti-excitatory actions. Methods: This randomized, double-blind, proof-of-concept study assessed the efficacy of the AMPA receptor antagonist, BGG492 (250 mg), vs placebo and sumatriptan (100 mg), in 75 subjects with acute migraine attacks. Efficacy was measured using the Patient Migraine Diary. Pharmacokinetic and safety data were collected. Results: Improvement from severe/moderate to mild/no headache pain (primary response) was reported in 58%, 58%, and 54% of BGG492-treated subjects at 2, 3, and 4 hours post-dose ( p = 0.2, 0.5, and 0.5 vs placebo), respectively, compared with 68%, 84%, and 92% sumatriptan-treated subjects, and 40%, 48%, and 44% in the placebo group. Percentages of subjects with ≥ 2-point improvement in pain score from baseline at 2 hours were 29%, 40%, and 16% for BGG492, sumatriptan, and placebo, respectively. Pain-free response at 2 hours was reported for 25%, 24%, and 16% of BGG492, sumatriptan, and placebo subjects, respectively. Adverse events were reported by 80%, 56%, and 60% of BGG492, sumatriptan, and placebo subjects, respectively. Conclusions: Proof-of-concept criterion was not met (≥ 25% BGG492 subjects with a primary response vs placebo at two timepoints). BGG492 was comparable to sumatriptan in terms of pain-free response.